Slovak Republic : Report on the Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents an Update to the Report on the Observance of Standards and Codes (ROSC) on Fiscal Transparency for the Slovak Republic. The 2003 ROSC update noted important further progress by Slovakia in bringing fiscal transparency close to international best practice, including by improving the coverage and availability of fiscal information; advancing work on international reporting standards; and improving the reporting of contingent liabilities and expenditure arrears. The government has clarified financial relations with state-owned enterprises, applying an ex ante dividend policy in preparing the public administration budget for 2005-07.